Rollover Stability Models for Three-Wheeled Vehicle Design - Ojolo, S. J.; Ajayi, O. O.; Asuelinmen, G. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
The current commercial  three-wheeled vehicles (TWVs) in the market are rollover unstable, with adverse effects on life and property.  This places limitation on their speed and usage, even though they are fuel efficient, cheap and generate about 33% of green gases per rider when compared with four-wheeled vehicles.This work derived mathematical models for the analysis of the stability of the three-wheeled vehicle (TWV). Based on these models, the test method for rollover stability was adopted. Rollover test was carried out on a TWV on Nigerian road. The results showed that the vehicle is unstable with respect to rollover stability. The test procedure if adopted and legislated upon, would significantly enhance safety of life and property of the population. Moreover, the speed and usage of the vehicle for both private and commercial purposes will be enhanced.